2019
DOI: 10.3390/met9060698
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Chip Formation in Orthogonal and Oblique Slow-Rate Machining of EN 16MnCr5 Steel

Abstract: In today's unmanned productions systems, it is very important that the manufacturing processes are carried out efficiently and smoothly. Therefore, controlling chip formation becomes an essential issue to be dealt with. It can be said that the material removal from a workpiece using machining is based on the degradation of material cohesion made in a controlled manner. The aim of the study was to understand the chip formation mechanisms that can, during uncontrolled processes, result in the formation and propa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…In the preliminary research of the authors [13], where the changes in temperature and microhardness of a chip root were evaluated, the angle of tool cutting edge inclination appeared to be an insignificant parameter. However, regarding changes in the chip shape, the angles of tool cutting edge inclination λ s and tool cutting edge κ r were the most important parameters.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the preliminary research of the authors [13], where the changes in temperature and microhardness of a chip root were evaluated, the angle of tool cutting edge inclination appeared to be an insignificant parameter. However, regarding changes in the chip shape, the angles of tool cutting edge inclination λ s and tool cutting edge κ r were the most important parameters.…”
Section: Discussionmentioning
confidence: 97%
“…However, orthogonal cutting is only a particular case of oblique cutting, such that any analysis of orthogonal cutting can be applied to oblique cutting. Oblique cutting is a common type of three-dimensional cutting used in the machining process [13].…”
Section: State Of the Artmentioning
confidence: 99%
“…Combined (experimental, analytical, numerical model, etc.) [3,[6][7][8][12][13][14][15][16][18][19][20]22,25,26] As can be readily observed, the experimental and empirical approach is the dominant methodology of failure investigation. In addition, the emergence of numerical simulation, using finite element modeling (FEM), tends to be very popular in the prediction of material behavior and potential failure prevention.…”
Section: Contributionsmentioning
confidence: 99%
“…Reference Structural and pipeline steels [1,5,9,13,16,20,22,27] Cast iron [14,19] Special resistance and stainless steels [3,4,9,11,17,18,21,23,24] Wear resistant coatings and surface layers [24,27]…”
Section: Materials Typementioning
confidence: 99%
“…For a long time, people have been committed to the research on rules of change in chip morphology and on modeling techniques under different processing conditions and have made fruitful achievements. For instance, through his experimental observation of chip morphology in the machining of EN16MnCr5 Steel with the straight double-edged tool, Monkova et al [11] found that the larger the cutting thickness and the edge inclination angle, the longer the chip. Polvorosa et al [12] compared the tool wear and its corresponding chip morphology when turning Alloy 718 with cemented carbide inserts.…”
Section: Introductionmentioning
confidence: 99%